Motor efficiency prediction of quality of work techniques involved in sport dance - Lukic, A.; Gerdijan, N.; Bijelic, S.; Zagorc, M.; Radisavljevic, L. (Serbian Journal of Sports Sciences, 2012)
With respect to the importance of dance technique for the dance class and the fact that achieving a good result and winning, especially in younger dance classes, is based on good technical preparation, it can be concluded that the training process should be oriented towards the development of motor skills that enable the dancer to prepare better technically. Detection and diagnosis of those motor skills which are important for the quality of technique of Latin American dances will redirect the preparation of trained dancers significantly, adding to the extensity and intensity of development and improving the dominant abilities. This was the main aim of the present study, conducted on dance sport competitors aged 12 to 15. The results indicated a wide range of motor skills on which the quality of the technique in Latin American dances depend, and singled out coordination, explosive power, and the ability to express complex rhythmic structures as dominant.